Old Yukon : tales, trails, and trials - Wickersham, James, 1857-1939 (Classic reprint series (Fairbanks, Alaska), 2009)
In this humorous and upbeat memoir, James Wickersham describes his career as a pioneer judge and later as a congressional representative assigned to a vast, snow-covered district, extending over 300,000 square miles in the undeveloped Alaska Territory. Wickersham's many adventures include traveling by dogsled over hundreds of miles through snow-covered mountains; serving as judge for the trials of many famous outlaws in the midst of the gold strikes; and hunting, mining, and climbing in his local Alaska wilderness. Though he was instrumental in the early history of Alaska, and his legacy is e.